1994
DOI: 10.3171/jns.1994.80.3.0433
|View full text |Cite
|
Sign up to set email alerts
|

The effect of surgery on the severity of vasospasm

Abstract: Intracranial aneurysm surgery performed between 4 and 12 days after subarachnoid hemorrhage (SAH) has been associated with an increased risk of delayed cerebral ischemia and poor outcome compared to surgery performed before or after this time. To investigate whether this increased risk is due to aggravation of vasospasm, the angiograms obtained before and after surgery in 56 patients operated on at various times after aneurysmal SAH were studied. Vasospasm was quantitated by measuring the diameters of intracra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
23
1
2

Year Published

1995
1995
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(28 citation statements)
references
References 30 publications
2
23
1
2
Order By: Relevance
“…SAH results in decreased cerebral blood flow (CBF) and impairs autoregulatory function, which makes the brain more sensitive to retraction and to fluctuations in blood pressure and cardiac output 7) . So, initial endovascular coiling of aneurysm followed by hematoma evacuation through burrhole was considered reasonable treatment option for this patient and achieved a tolerable outcome.…”
Section: Discussionmentioning
confidence: 99%
“…SAH results in decreased cerebral blood flow (CBF) and impairs autoregulatory function, which makes the brain more sensitive to retraction and to fluctuations in blood pressure and cardiac output 7) . So, initial endovascular coiling of aneurysm followed by hematoma evacuation through burrhole was considered reasonable treatment option for this patient and achieved a tolerable outcome.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, younger patients are more likely to experience vasospasm than the others. 4,33 In this study, WFNS clinically low grades (I and II) were predictors of symptomatic vasospasm. Using the Hunt and Hess grades, Rabb et al 4 reported similar results, while in another study the Hunt and Hess clinical grades 30 were not found to be predictors of vasospasm.…”
Section: Prognostic Factors Of Cerebral Vasospasmmentioning
confidence: 99%
“…Our findings are similar to those of other studies. For example, Yoshimoto and Kwak 49 and Macdonald et al, 28 who used DSA to diagnose CV, observed that a younger age is associated with a greater frequency of severe angiographic CV. Magge et al 29 also reported that the likelihood of severe vasospasm was greater with a younger age; patients with severe angiographic CV were on average 9 years younger than those with no CV.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have suggested that younger adults have a higher risk for developing CV. 28,29,49 There is no clear consensus, in part because CV can be diagnosed with different modalities and approaches, including digital subtraction angiography (DSA), CT angiography, transcranial Doppler (TCD) ultrasonography, and evaluation of clinical symptoms. The few published studies on CV in children have concluded that this group has a relatively high rate of CV diagnosed by angiography.…”
mentioning
confidence: 99%